The use of carglumic acid in hyperammonemia secondary to bacterial overgrowth in lately diagnosed Hirschsprung disease - Tala Shalakhti; Yazan O. Al Zu'bi; Ahmed H. Al Sharie; Ahmad K. Abdulraheem; Amjad Al-Salhi; Ahmed N. Barakat; Eyad Altamimi (Elsevier, 2022)
Hirschsprung disease is associated with significant bacterial proliferation and colonic dysbiosis leading to life threating hyperammonemia. In this report, we highlight the use of carglumic acid; a synthetic ammonia scavenger in hyperammonemia secondary to bacterial overgrowth in Hirschsprung disease. A 33-month-old female patient with a history of delayed passage of meconium presented with constipation, vomiting, abdominal distention, and an altered level of consciousness. Physical examination revealed a puffy face, non-pitting edema and distended, rigid, non-tender abdomen with faint bowel sounds. Further investigations showed anemia, hypoalbuminemia, hyperammonemia, prolonged prothrombin time and partial thromboplastin time alongside a normal liver enzymes panel. Abdominal X-ray imaging revealed severely dilated bowel loops reassembling obstruction and impending perforation. A lower gastrointestinal contrast study revealed a classical picture of Hirschsprung disease with a transition zone at the rectosigmoid. Urgent surgical intervention was performed resecting the distended part of the sigmoid colon applying an end colostomy with a distal end closure was done. The diagnosis of Hirschsprung disease was confirmed histopathologically. The patient was started on oral antibiotics and carglumic acid 600 mg q12h for the state of hyperammonemia and the unavailability of sodium benzoate. After its administration the ammonia levels dropped from 302 μmol/L to a nadir of 46 μmol/L. Taking into consideration our case carglumic acid proved to be an effective ammonia scavenger in such cases.